2020
DOI: 10.1111/1468-4446.12787
|View full text |Cite
|
Sign up to set email alerts
|

From starving artist to entrepreneur. Justificatory pluralism in visual artists' grant proposals

Abstract: Inspired by French pragmatism and using Bourdieu's notion of “refraction” as an indication of a field's autonomy, we explore in‐depth what kinds of justifications visual artists deploy to legitimate their requests for government money. Based on 494 government grant proposals from visual artists between 1965 and 2015 in Belgium, we find six such justifications. The reputational, esthetic, and romantic justifications are grounded in autonomous criteria of worth, such as artistic CVs, the work of art itself, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In the 21st century, the shift from visual culture to fine art education has brought about new educational trends, providing unlimited creativity and possibilities for fine art creation, which continue to permeate in the field of fine art, bringing about marked changes in the goals, fields, methods, and evaluation of education [9,10]. Facing the future social life, students in colleges and universities are required to continuously improve their own literacy, as well as their creative thinking, critical visual literacy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the 21st century, the shift from visual culture to fine art education has brought about new educational trends, providing unlimited creativity and possibilities for fine art creation, which continue to permeate in the field of fine art, bringing about marked changes in the goals, fields, methods, and evaluation of education [9,10]. Facing the future social life, students in colleges and universities are required to continuously improve their own literacy, as well as their creative thinking, critical visual literacy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent times -particularly from 1996 onwards -applicants were far more likely to use heteronomous (academic, socially engaged and entrepreneurial) strategies and abandoned the suffering artist discourse. This shift was not only in line with changes such as the social (Bishop, 2006) and scientific turns (Peters and Roose, 2020;Laermans, 2018;Schinkel, 2010) in the art field at the time. It also coincided with a major change in Flemish cultural policy in the early 1990s, namely, its increased focus on heteronomous values such as entrepreneurialism and social impact, and banishment of its former reliance on social welfare considerations for the evaluation of artists' proposals.…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…In previous work, we found that justificatory discourse in grant proposals followed developments from the field of contemporary art and cultural policy (Peters and Roose, 2020) – that is, from the ‘space of possibles’. Before the 1990s, artists predominantly used ‘autonomous’ strategies to substantiate their claims for government money, focusing on reputational, aesthetic and romantic justifications in their proposals.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
See 2 more Smart Citations